High Throughput Screening with Multiphoton Excitation - LAKOWICZ, JOSEPH R. (J Biomol Screen, 1999)
Fluorescence detection is extensively used in high throughput screening. In HTS there is a continuous migration toward higher density plates and smaller sample volumes. In the present report we describe the advantages of two-photon or multiphoton excitation for HTS. Multiphoton excitation (MPE) is the simultaneous absorption of two long-wavelength photons to excite the lowest singlet state of the fluorophore. MPE is typically accomplished with short but high-intensity laser pulses, which allows simultaneous absorption of two or more photons. The intensity of the multiphoton-induced fluorescence is proportional to the square, cube, or higher power of the instantneous photon flux. Consequently, two-photon or multiphoton excitation only occurs at the focal point of the incident beam. This property of two-photon excitation allows the excited volume to be very small and to be localized in the center of each well in the HTS plate. We show that two-photon-induced fluorescence of fluorescein can be reliably measured in microwell plates. We also show the use of 6-carboxy fluorescein as a pH probe with two-photon excitation, and measure 4′–6-diamidino-2-phenylindole (DAPI) binding and two-photon-induced fluorescence. In further studies we measure the time-dependent intensity decays of DAPI bound to DNA and of calcium-dependent fluorophores. Finally, we demonstrate the possibility of three-photon excitation of several fluorophores, including indole, in the HTS plate. These results suggest that MPE can be used in high-density multiwell plates.